The sedimentary environment in the Ljubljansko barje basin during the pile-dwelling period - Tomaž Verbič (Arheološki Vestnik, 2011)
Geological processes on the Ljubljansko barje basin after the Last Glacial Maximum are known merely on a general level. At few points more detailed circumstances are known, but this information is fragmented spatially and temporally. While artefacts from the archaeological sites were studied in detail, the sediments were mostly only imperfectly described. Better understanding of the evolution of the environment requires accurate study of these sediments and buried soils, and detection of evident stratigraphical hiatuses.